of students pedagogical skills to physical education - Galina Bezverkhnya; Mykola Mayevsky (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to describe the motivation to physical education of pedagogical skills girls in the context of motivation to learn and motivation to succeed. Material and Methods: 90 second-year students of pedagogical specialties were researched (30 girls from pre-school education, philological and economic faculties) Pavlo Tychyna Uman State Pedagogical University. Results: described the motivation of students in physical education by the analysis of involvement of subject and the target set. Student's motivation to learning activities and their level to success motivation were additionally investigated. Conclusions: is outlined reason of not formed internal motivation of students' physical training in general psychological orientation of the girls that sufficiently shown in context of motivation to learn and progress.